A kind of active covering material of bottom mud and its preparation method and application

The active cover material of the bottom sludge is prepared by hydrothermal method of fly ash and calcium carbide slag, activate the vitreous structure of fly ash, and form calcium silicate and calcium aluminum garnet with high adsorption performance, solving the problem of endogenous phosphorus release in the bottom sludge , realizes efficient phosphate fixation and resource circulation, and meets the needs of lake eutrophication management.

CN118341410BActive Publication Date: 2024-12-17CHANGJIANG SURVEY PLANNING DESIGN & RES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410385010.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-01
Publication Date
2024-12-17
Estimated Expiration
2044-04-01

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively control the release of endogenous phosphorus in the bottom sludge, resulting in the continued eutrophication problem of lakes. Traditional covering materials such as calcium carbide slag have ecological hazards and limited application, and insufficient adsorption performance of fly ash, making it difficult to achieve effective phosphate fixation.

Method used

Fly ash and calcium carbide slag are prepared by hydrothermal method to form a bottom sludge active covering material, and the glass structure of fly ash is activated by using a strong alkali environment to generate calcium silicate and calcium aluminum garnet with high specific surface area to improve phosphoric acid Salt adsorption properties and form a stable mineral structure through hydrothermal reaction, delaying Ca2+ release and achieving long-term fixation of phosphate.

Benefits of technology

It has achieved low-cost, environmentally friendly phosphate adsorption and fixation, reduced the phosphate release efficiency, reaching more than 97%, meeting the needs of phosphorus pollution repair in water bodies and bottom sludge, and realizing resource recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118341410B_ABST
    Figure CN118341410B_ABST
Patent Text Reader

Abstract

The present invention discloses a sediment active covering material and a preparation method and application thereof, and belongs to the technical field of sediment covering material preparation and water treatment. The sediment active covering material is mainly prepared from fly ash and carbide slag by a hydrothermal method. The present invention mixes fly ash and carbide slag for hydrothermal modification to prepare a low-cost, environmentally friendly sediment active covering material with excellent phosphate adsorption performance, and is successfully used to repair the P pollution problem in water bodies and sediments, achieving a win-win situation of environmental protection and resource recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sediment covering material preparation and water treatment, and in particular relates to a sediment active covering material and a preparation method and application thereof. Background Art

[0002] For a long time, phosphorus inhibition has been considered the most important limiting factor for lake eutrophication. Therefore, controlling the concentration of phosphorus in lakes is the key to lake eutrophication control. However, studies have shown that even after exogenous phosphorus is effectively controlled, the problem of lake eutrophication will still persist for decades due to the release of endogenous phosphorus in sediments. Therefore, controlling the release of endogenous phosphorus in sediments is considered to be a comprehensive method for controlling lake eutrophication.

[0003] So far, many researchers at home and abroad have developed many technologies to control the release of endogenous phosphorus in sediments, mainly including sediment dredging, in-situ chemical injection, in-situ covering and other technologies. Among them, in-situ covering technology is considered to be a technology that can effectively control the endogenous pollution problem of lakes. Its principle is to use covering materials to fix soluble phosphate (SRP), improve the binding ability of sediments and SRP, and minimize the release of P into the water body. The traditional in-situ covering technology is to cover a large amount of sand and gravel on the polluted sediment to achieve physical masking. However, this method will change the hydraulic conditions of rivers and lakes, so its application range is limited. Therefore, many scholars have turned their attention to active covering materials. Active thin layer covering uses adsorbent materials with excellent phosphate adsorption properties as covering materials, covering the surface of sediments, or mixing with sediments. This method can not only adsorb phosphates in the overlying water, but also effectively fix phosphates in sediments, reducing the risk of phosphates in sediments being released into the overlying water. Common active covering materials mainly include minerals or industrial waste residues with high content of aluminum, calcium and iron compounds. Among them, Ca-rich materials are often used as capping materials to fix P in sediments.

[0004] Carbide slag is the industrial waste residue from the hydrolysis of carbide to produce acetylene. It is a promising material that can solve many of the above-mentioned environmental problems and meet environmental requirements. However, once carbide slag comes into contact with water, it will release a large amount of Ca2+ and OH-, causing the pH of the water body to rise. On the one hand, it is easy to cause harm to the ecosystem, so it is not suitable for direct use. On the other hand, the rapid reaction of carbide slag with water will produce a physical barrier, resulting in weak permeability of Ca2+ in sediments, so it has not been widely used as a sediment capping material.

[0005] Fly ash is one of the largest industrial solid wastes currently discharged in my country. According to research, my country's current use of fly ash is still mainly concentrated in low-value utilization areas, such as construction, agriculture and other industries. Therefore, seeking some high-value utilization methods is crucial for solid waste treatment and environmental improvement. Fly ash has advantages such as large specific surface area and good adsorption performance, but its special glass structure and relatively stable properties make it difficult to achieve a good adsorption effect in solution. Summary of the invention

[0006] In view of the technical problems existing in the prior art, the purpose of the present invention is to propose a sediment active covering material and a preparation method and application thereof. The present invention mixes fly ash and carbide slag for hydrothermal modification to prepare a low-cost, environmentally friendly sediment active covering material with excellent phosphate adsorption performance, and is successfully used to repair the P pollution problem in water bodies and sediments, achieving a win-win situation of environmental protection and resource recycling.

[0007] To achieve the above object, the present invention is implemented by the following technical solutions:

[0008] The invention discloses a bottom mud active covering material, which is mainly prepared from fly ash and carbide slag through a hydrothermal method.

[0009] Preferably, the mass ratio of the fly ash to the carbide slag is 4:1.

[0010] A method for preparing a sediment active covering material, comprising:

[0011] Step 1: Dry the fly ash and carbide slag separately, grind and screen them, and place them in a dryer for later use;

[0012] Step 2: weigh the pretreated fly ash and carbide slag according to the designed mass ratio, mix and stir to fully mix; then transfer the mixture into a reactor;

[0013] Step 3: Add deionized water to the mixture, stir again to make it evenly dispersed, then tighten the reactor containing the mixed material and send it into an oven for hydrothermal reaction;

[0014] Step 4: After the hydrothermal reaction is completed, the material is taken out and washed with deionized water for multiple times until the pH value of the supernatant reaches between 7 and 8;

[0015] Step 5: Separating the material from the supernatant to obtain a solid material;

[0016] Step six: drying the obtained solid material to obtain the bottom mud active covering material.

[0017] The preparation method cleverly uses fly ash and carbide slag as the main raw materials, and transforms them into active covering materials through a specific treatment process, thereby achieving efficient resource utilization of waste, reducing environmental pollution, and reducing material costs. The preparation method is simple in process, easy to operate, does not require complex equipment, and is conducive to large-scale production and application.

[0018] Preferably, the screening mesh number in step 1 is 80 meshes. The 80 mesh screening ensures that the fly ash and carbide slag particles have moderate fineness, which is beneficial to subsequent reaction and adsorption.

[0019] Preferably, the reaction kettle in step 2 is a polytetrafluoroethylene container.

[0020] Preferably, the hydrothermal temperature in step three is 140-160° C., and the hydrothermal time is set to 4-6 h.

[0021] Preferably, the hydrothermal temperature in step 3 is 140° C., and the hydrothermal time is set to 4 hours. Such conditions can promote full reaction inside the material, improve the reaction efficiency and performance of the material, form a stable mineral structure, and thus enhance the adsorption and fixation capacity of phosphorus pollutants.

[0022] Preferably, a vacuum filtration device is used to separate the material from the supernatant in step 5. The vacuum filtration device can effectively separate the solid material from the supernatant, improve the separation efficiency, and facilitate subsequent processing.

[0023] Preferably, the drying temperature in step 1 and step 6 is 105° C. and the drying time is 24 hours. The drying temperature is set at 105° C., which can effectively remove moisture and avoid high temperature-induced structural damage to the material, thereby maintaining its activity.

[0024] The invention discloses an application of a sediment active covering material in the restoration and control of phosphorus pollution in water bodies and sediments. The prepared sediment active covering material shows good application prospects in the restoration and control of phosphorus pollution in water bodies and sediments, and can effectively reduce the concentration of phosphorus and alleviate the eutrophication problem.

[0025] Compared with the prior art, the technical solution provided by the present invention has the following advantages and beneficial effects:

[0026] (1) The present invention uses carbide slag as an alkaline activator and hydrothermally prepares fly ash / carbide slag-based active covering materials together with fly ash, thereby converting fly ash and carbide slag into high value-added products, realizing the resource utilization of fly ash and carbide slag, and providing a new way for thermal power plants and acetylene production and manufacturing industries to treat fly ash and carbide slag.

[0027] (2) In the fly ash-deionized water hydrothermal system, carbide slag is introduced to provide a strong alkaline environment, which activates and decomposes the dense structures such as glass in the fly ash, and releases a large amount of SiO4 4- , AlO4 5- , and the free Ca released from carbide slag 2+ In a strong alkaline atmosphere, a polymerization reaction occurs to generate calcium silicate, grossular garnet and Ca-containing cross zeolite ( Figure 3 );Remaining free Ca 2+ It absorbs a large amount of CO2 in an alkaline atmosphere to form calcium carbonate ( Figure 3 ). Among them, the calcium-containing cross zeolite increases the specific surface area of ​​the material, making the specific surface area of ​​the material from 1.94m 2 / g increased to 27.61m 2 / g, and provide a large number of phosphate adsorption active sites, greatly improving the adsorption performance of fly ash; calcium carbonate, calcium silicate and grossular garnet delay the adsorption of Ca 2+ The release flux is 0.87mg / (g·h) (Ca in carbide slag 2+ The release flux was reduced to 0.16 mg / (g·h) (Ca 2+ Release flux), so that it can fully react with the sediment and achieve long-term and effective fixation of SRP in the sediment.

[0028] (3) The maximum adsorption capacity of phosphate by the fly ash / carbide slag-based active covering material prepared by the present invention can reach 35.32 mg / g, and its efficiency in reducing the release of phosphate in the sludge is more than 97%. It has an excellent effect of fixing phosphate in the sludge, which is beneficial to the recovery and resource utilization of fly ash and carbide slag. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a diagram showing the effect of the active covering material of the sediment on the SRP concentration of the overlying water in an embodiment of the present invention.

[0030] Figure 2 This is a graph showing the effect of the active sediment covering material on the reduction rate of SRP released from the sediment in an embodiment of the present invention.

[0031] Figure 3 This is the XRD spectrum of the active covering material of the bottom mud in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.

[0033] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0034] Example 1

[0035] This embodiment provides a fly ash / carbide slag based mud active covering material, and the preparation method thereof is as follows:

[0036] (1) Dry the fly ash and carbide slag in a 105°C oven for 24 hours, grind them through an 80-mesh sieve, and place them in a dryer for later use.

[0037] (2) Weigh the materials according to the mass ratio of 80% fly ash: 20% carbide slag, stir for 5 minutes to fully mix, and transfer them into a 50mL polytetrafluoroethylene container.

[0038] (3) Add 25 mL of deionized water, stir for 5 min to fully mix, tighten the reactor, and place it in a 160°C oven for hydrothermal heating. The hydrothermal time is set to 6 h.

[0039] (4) After the hydrothermal reaction is completed, the material is taken out and washed with deionized water for multiple times until the pH value of the supernatant is 7-8. Further, a vacuum filtration device is used to separate the material and the supernatant. The solid material is obtained and sent to a 105°C oven for drying for 24 hours to obtain the final product, fly ash / carbide slag-based mud active covering material.

[0040] The dried fly ash / carbide slag base mud active covering material was ground through an 80-mesh sieve, and the product was weighed according to a solid-liquid ratio of 2g / L, mixed thoroughly with 40mL of potassium dihydrogen phosphate solution (100mg / L), placed in an air bath oscillator at 25°C, reacted for 24h, and the oscillator speed was set to 150r / min.

[0041] After adsorption, the mixture was filtered using a 0.45 μm PES filter to obtain a clear supernatant. The phosphate concentration of the supernatant was determined according to the "Determination of Total Phosphorus in Water - Ammonium Molybdate Spectrophotometry" (GB 11893-89), and the phosphate adsorption capacity of the product was calculated according to formula (1). The specific phosphate adsorption capacity was 33.77 mg / g.

[0042]

[0043] In the formula, Q e (mg / g) is the adsorption capacity, C (mg / L) is the initial concentration of phosphate; C e (mg / L) is the residual phosphate concentration in the supernatant after adsorption; m (g) is the added mass of the adsorbent; V (mL) is the volume of phosphate added during adsorption.

[0044] Example 2

[0045] The same method as in Example 1 is used, except that: in step (3), the mixture of fly ash and carbide slag is transferred to a 50 mL polytetrafluoroethylene container, and 25 mL of deionized water is added, and stirred again for 5 min to fully mix. Finally, the reactor is sent to an oven for hydrothermal reaction. The hydrothermal time is set to 4 h, and the hydrothermal temperature is set to 160° C. The phosphate adsorption capacity of the product is 32.17 mg / g.

[0046] Example 3

[0047] The method of Example 1 is the same as that of Example 1, except that the hydrothermal temperature in step (3) is set to 140°C and the hydrothermal time is set to 4 hours. The phosphate adsorption capacity is 35.32 mg / g. This example has the best phosphate adsorption capacity and can effectively prevent the release of P in the sediment.

[0048] Comparative Example 1

[0049] The same method as in Example 1 is used, except that in step (2), materials are weighed according to the mass ratio of (0%) carbide slag: (100%) fly ash. The phosphate adsorption capacity thereof is measured to be 3.35 mg / g.

[0050] Comparative Example 2

[0051] The same method as in Example 1 is used, except that in step (2), materials are weighed according to the mass ratio of (0%) carbide slag: (100%) fly ash, and in step (3), 25 mL of NaOH solution (2 mol / L) is added. The phosphate adsorption capacity is measured to be 7.27 mg / g.

[0052] Experimental Example 1

[0053] (1) The sediment used in the experiment was sampled from Yanxi Lake in Ezhou, Hubei Province. The original sediment was preliminarily screened to remove aquatic plant residues and large sand and gravel. It was further dried in a 105℃ oven for 72 hours.

[0054] (2) Use a multifunctional high-speed shredder model YB-2500A to pulverize the dried sludge and pass it through an 80-mesh sieve.

[0055] (3) Add potassium dihydrogen phosphate solid to the sediment to pollute the sediment. Finally, the SRP (Total Phosphorus) content in the sediment was measured by ultraviolet spectrophotometry to be 55.38 mg / g. After one month of cultivation, the polluted sediment was dried again, crushed and ground to pass through an 80-mesh sieve.

[0056] (4) Weigh 100 g of sludge and place it into a 500 mL brown reagent bottle so that the sludge height is approximately 3 cm.

[0057] (5) Weigh about 10 g of the fly ash / carbide slag base mud active covering material prepared in Example 3, and slowly spread it on the bottom mud to keep its thickness at about 1 cm. Among them, the experimental group without adding covering material is named control group, and the experimental group with adding fly ash / carbide slag base mud active covering material (Example 3) is named experimental group.

[0058] (6) Use the siphon method to add 400 mL of deionized water, tighten the bottle cap and place it in a 25°C oven to conduct a bottom mud coverage experiment.

[0059] (7) 10 ml of overlying water was extracted using a syringe 3 cm above the mud-water interface, filtered using a 0.45 μm PES filter, and the SRP concentration in the filtrate was tested by UV spectrophotometry. The release reduction efficiency of the covering material on SRP in the sediment was calculated according to formula (2).

[0060]

[0061] Where φ(%) is the reduction rate, C0(mg / L) is the SRP concentration in the overlying water of the control group; C(mg / L) is the SRP concentration in the overlying water of the experimental group.

[0062] This experimental example explores the covering effect of fly ash / carbide slag based mud active covering material (Example 3) on phosphate in polluted mud. The results are as follows Figure 1 shown. Figure 1 The phosphate concentration in the overlying water after covering with fly ash / carbide slag base mud active covering material. It can be found that during the 10-day cultivation process, the phosphate concentration in the overlying water of the control group remained in the range of 4.84-7.90 mg / L, which is a relatively high concentration. In the experimental group, the phosphate concentration in the overlying water remained in a lower concentration range (0.02-0.20 mg / L), which was significantly lower than the control group, and could meet the surface water Class III water quality standard and lake (reservoir) Class IV water quality standard. In addition, from the reduction rate point of view ( Figure 2 ), the reduction rate of the experimental group was always maintained above 97%. These results show that the fly ash / carbide slag substrate mud active covering material provided in Example 4 of the present invention can effectively prevent the release of phosphorus in the sediment.

[0063] In summary, the fly ash / carbide slag based mud active covering material provided in this embodiment not only realizes the high-value utilization of industrial waste, but also provides an environmentally friendly and efficient solution for the remediation of water and mud phosphorus pollution.

[0064] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A sediment active covering material, characterized in that: The active sediment covering material is used to repair and control phosphorus pollution in water bodies and sediments. The active sediment covering material is mainly prepared from fly ash and carbide slag by a hydrothermal method. The mass ratio of the fly ash to the carbide slag is 4:

1. The active sediment covering material contains calcium-containing phillipsite. The method for preparing the sediment active covering material comprises: Step 1: Dry the fly ash and carbide slag separately, grind and screen them, and place them in a dryer for later use; Step 2: weigh the pretreated fly ash and carbide slag according to the designed mass ratio, mix and stir to fully mix; then transfer the mixture into a reactor; Step 3: Add deionized water to the mixture, stir again to make it evenly dispersed, then tighten the reactor containing the mixed material, and send it into an oven for hydrothermal reaction, the hydrothermal reaction temperature is 140-160° C., and the hydrothermal time is 4-6 hours; Step 4: After the hydrothermal reaction is completed, the material is taken out and washed with deionized water several times until the pH value of the supernatant reaches between 7 and 8; Step 5: Separating the material from the supernatant to obtain a solid material; Step six: drying the obtained solid material to obtain the bottom mud active covering material.

2. The active covering material for bottom mud according to claim 1, characterized in that: The screening mesh size in step 1 is 80 meshes.

3. The active covering material for bottom mud according to claim 1, characterized in that: The reaction kettle in step 2 is a polytetrafluoroethylene container.

4. The active covering material for bottom mud according to claim 1, characterized in that: The hydrothermal temperature in step 3 is 140°C and the hydrothermal time is set to 4h.

5. The active covering material for bottom mud according to claim 1, characterized in that: In step five, a vacuum filtration device is used to separate the material from the supernatant.

6. The active covering material for bottom mud according to claim 1, characterized in that: The drying in step 1 and the baking in step 6 are performed at a temperature of 105° C. and a time of 24 h.